2017
DOI: 10.1038/s41598-017-09644-w
|View full text |Cite
|
Sign up to set email alerts
|

Fungal lifestyle reflected in serine protease repertoire

Abstract: Fungi are able to switch between different lifestyles in order to adapt to environmental changes. Their ecological strategy is connected to their secretome as fungi obtain nutrients by secreting hydrolytic enzymes to their surrounding and acquiring the digested molecules. We focus on fungal serine proteases (SPs), the phylogenetic distribution of which is barely described so far. In order to collect a complete set of fungal proteases, we searched over 600 fungal proteomes. Obtained results suggest that serine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 106 publications
(82 reference statements)
8
93
1
2
Order By: Relevance
“…Moreover, the analysed exoproteases are aminopeptidases dipeptidyl peptidases and carboxypeptidases . Recently, Muszewska et al suggested that SPs are more pervasive in fungi than anticipated as 21/54 SPs depicted in MEROPS peptidase database are found in fungi. SUB6 was detected in T. verrucosum .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analysed exoproteases are aminopeptidases dipeptidyl peptidases and carboxypeptidases . Recently, Muszewska et al suggested that SPs are more pervasive in fungi than anticipated as 21/54 SPs depicted in MEROPS peptidase database are found in fungi. SUB6 was detected in T. verrucosum .…”
Section: Discussionmentioning
confidence: 99%
“…In Candida albicans the SPS system has also been implicated in immune evasion and nutrient acquisition, by sensing extracellular amino acids (68). Other expanded gene families include: pectinase gene families that may be involved in utilization of pectin as a nutrient in the plant phylloplane and a family of secreted subtilisin-like serine proteases previously linked with nutrient acquisition during soil-residency (69). Finally, carbohydrate-active enzyme (CAZyme) gene content was defined; all Protomyces species had similar and low number of CAZymes relative to other fungal pathogens, consistent with their small genomes and facultative-biotrophic pathogen lifestyles (70).…”
Section: Comparative Genomics Within the Protomycesmentioning
confidence: 99%
“…Homologs to known effectors, and effectors with conserved domains of virulence factors may have similar functions in C. tanaceti, for example, in penetration peg formation (cyclophllin) [130], phytotoxity induction (ceratoplatanin) [131] and adherence of the fungal structures to other organisms (hydrophobin) [132]. Most secreted proteases of C. tanaceti were serine proteases predicted to evade plant immune responses by degrading plant chitinases [22]. Subtilisins (S08) were the most abundant of these in C. tanaceti, similar to reports in other fungi [22].…”
Section: Discussion Genome and The Repeat Content Of Colletotrichum Tmentioning
confidence: 99%
“…Most secreted proteases of C. tanaceti were serine proteases predicted to evade plant immune responses by degrading plant chitinases [22]. Subtilisins (S08) were the most abundant of these in C. tanaceti, similar to reports in other fungi [22]. Subtilisins, with their alkaline optima, and the proteases in other subfamilies with acidic optima, such as A01, C13, G01, M20 and S10 [133], might enable C. tanaceti to degrade plant proteins across a wide pH range.…”
Section: Discussion Genome and The Repeat Content Of Colletotrichum Tmentioning
confidence: 99%
See 1 more Smart Citation